Currículo e pedagogia cultural no carnaval de Corumbá/MS: as baterias das escolas de samba e a produção de masculinidades. - Rêner de Melo Helena (2022)
Carnival is one of the biggest popular festivals held in Brazil. In Mato Grosso do Sul, the carnival in the city of Corumbá/MS, which is located in the Pantanal and on the Brazil-Bolivia border, is the most important in the Midwest region. This research aims to analyze the curriculum and cultural pedagogy in the production of masculinities in the samba schools of Corumbá carnival. This is a qualitative study that makes use of online ethnography and includes semi-structured interviews. Seven men linked to carnival and to the city's samba schools were selected. In the introduction, a brief overview of Corumbá’s carnival is presented. In the second chapter, the literature review is presented. In the third chapter, the theoretical framework and methodology are exposed, pointing out the relationships between the researcher and the interlocutors’ presentation. In the fourth chapter, education, gender, curriculum and pedagogy of masculinities produced in the samba schools of Corumbá are discussed. It is concluded that the batteries of samba schools in Corumbá produce specific masculinities on the Brazil-Bolivia border in a curricular and pedagogical way involving feelings, practices and attitudes taken as men.